Penilaian Kualitas Website E-Government Pejabat Pengelola Informasi dan Dokumentasi (PPID) Dengan Dimensi e-GovQual (Studi Pada Dinas Komunikasi dan Informatika Pemerintah Kota Probolinggo) - Sri Eko Wahyudi; Aryo Pinandito; Mochamad Chandra Saputra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Public information is information resultant, saved, and / or received from with regard to the organizers and the implementation of other public bodies in accordance with the Act as well as other information relating to the public interest. Based on the Law of the Republic of Indonesia no. 14 years 2008 about public information openess explain that every one have right to get information as written in the Law on public Information. Based on result of interview with someone from Kominfo's Probolinggo city, dissemination information by "Pejabat Pengelola Informasi dan Dokumentasi (PPID)â€ Probolinggo city with two manners, that is dissemination informations with electronic and non-electronic. in the spread informations via electronic in website untill now not been evaluated. evaluation is an effort to carry out the development and improvement of the system To see the extent to which the website provides convenience to the community then be required for analysis of the extent to which the quality of the website. Analysis of the quality of government websites can be done using e-GovQual dimensional approach which will then be determined priority to the problems found using Importance Performance Analysis. after found problems priority will be given recommendations for websites improvement using Heuristic Evaluation approach. From the results of existing recommendations, so it can be used as a reference by the Government of Probolinggo to develop the website so even easier to use by the public. Based on the results, there are fact that the level of satisfaction of the user community in using the website PPID Kota Probolinggo on perception of the average of 2.99 and an average interest rate of 4.07 on a scale of 5. But there are parameters of perception based on instrument e-GovQual question, ie in that ease of use with value 2.7 which indicates dissatisfaction with the structure of the website. In addition, there are parameters of perception based on instrument e-GovQual question on ease of use, reliability and the content and appearance with a value of 4.2 which indicates the importance of the ability to make adjustments, perform timely service delivery, speed of transactions and completeness data and information on the website.